Cultural Diversity impact on public project success & Innovation role in UAE public sector - AL SUWAIDI, RAFIA SULTAN (2017)
This research paper investigates the impact of cultural diversity on public project success as well as innovation ideas it can help generate in the UAE public sector. Furthermore, this research aims to find the relation between cultural diversity and its impact on project success. In this research, different criteria’s have been found that will have an impact on project success which will reduce the effectiveness of teamwork which will reduce the chances of the project being a success. Some of the challenges that have been found are leadership, project management, open communication, top management support, rewards etc. By not providing the proper climate needed for innovation as well as managing the group of people from different cultures, teams can become inefficient. This paper identified 8 factors that will influence project success rate; leadership, knowledge management, rewards, innovation, top management support, empowerment and cultural diversity. Questionnaire was handed to a public transport organization and its employees had to compulsory fill in their answers. 70 questionnaires were handed to the employees and the percentage was found using pie chart. Furthermore, the bar chart also has been provided which shows the frequency of the people in terms of the answers that they gave.